Empowering Education Through Virtual Reality-Driven Course and Examination System - YILDIZ, MEHMET SEDAT; MUSTAFAOĞLU, BERKAY; ELMASRY, WİSAM (IEEE, 2025)
This paper presents the development of "Virtual Academy", a Virtual Reality (VR)-based application designed to ensure uninterrupted access to education, particularly in scenarios where physical attendance in classrooms is challenging. The platform enables students to log in via personal credentials, granting access to assigned courses within an immersive virtual classroom. Teachers and students interact in real-time, with educators leveraging audiovisual tools to enhance the learning experience. The system also supports lesson recording for future reference, evaluates the performance of the students via designated exams, and facilitates a seamless transition to remote learning. By harnessing modern VR technology, Virtual Academy enhances educational continuity and offers an interactive and engaging alternative to traditional learning environments.
International Congress on Human-Computer Interaction, Optimization and Robotic Applications, Proceedings
Keywords: Human-Computer Interaction; Immersive Experience; Real-time Examination System; Remote Education; Virtual Reality